EFFECT OF AQUEOUS EXTRACT OF CAPSICUM BACCATUM ON MORTALITY AND OVIPOSITION OF Tetranychus ludeni (ACARI: TETRANYCHIDAE) - LUCINI, Tiago; SCABENI, Cléverson; DEDORDI, Cássio; HIROSE, Edson; SHIOMI, Humberto Franco (Scientia Agraria, 2010)
Current public concern about the adverse effects of agricultural chemicals on health and the environment has generated interest in alternative control methods, like the botanical extracts active against arthropods. The objective of this work was to assess the toxicity of aqueous pepper extract of Capsicum baccatum (Magnoliopsida: Solanaceae) on the red spider mite Tetranychus ludeni (Acari: Tetranychidae). Seeds of C. baccatum were dried, powdered and suspended in distilled water at concentrations of 0 (control), 0.5, 1.0, 2.0, 4.0 and 8.0 dag dm-3. common bean leaf discs were dipped in the different concentration of extract. Ten adult females of T. ludeni were placed on each disc, and kept in a room (25 ± 2 º C, photoperiod 12 h). After 24 h, 48 and 72h the mortality and the number of eggs oviposited were assessed. Mortality did not vary among concentrations, but the oviposition was negatively affected in the highest concentrations (4 and 8%) in the order of 25.4% to 34.7% respectively. The seed extract of C. bacattum has a potential use in controlling red spider mite.